The Influence Of The Tourism Sector On Labor Absorption In Bengkulu Province From 2014 To 2024 - Maisarah, Ria; Hasan , As’ad; Siswanto , Ariel (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the influence of the tourism sector on labor absorption in Bengkulu Province during the 2014–2024 period. The tourism sector is measured through three main indicators: the number of tourist attractions, the number of tourists, and the minimum wage level. The method used in this study is multiple linear regression analysis, accompanied by classical assumption tests, including normality, autocorrelation, multicollinearity, and heteroscedasticity tests. The classical assumption test results indicate that the data are normally distributed, free from autocorrelation, have no multicollinearity, and show no signs of heteroscedasticity. The regression results show that, partially, only the minimum wage has a significant effect on labor absorption (significance value 0.001 < 0.05). Meanwhile, the number of tourist attractions and the number of tourists do not have a significant partial effect. However, simultaneously, the three tourism sector indicators have a significant influence on labor absorption in Bengkulu Province, as indicated by the F-value of 55.192 > F-table value of 4.10, with a significance level of 0.000 < 0.05. The Adjusted R² value of 0.942 indicates that 94.2% of the variation in labor absorption can be explained by the tourism sector, while the remaining 5.8% is influenced by other factors outside the model. These findings highlight the importance of the tourism sector in job creation and in promoting regional economic growth.